Peran Serikat Pekerja dan Perjanjian Kerja dalam Meningkatkan Kinerja Karyawan: Studi pada PT Panasonic Manufacturing Indonesia - Ashofi, Fahri Ali (Journal of Social Movements, 2025)
This research aims to investigate the influence of labor unions and employment agreements on employee performance at PT. Panasonic Manufacturing Indonesia. Labor unions and employment agreements are two factors that can affect working conditions and employee motivation, subsequently impacting their performance. The research method employed is quantitative research, based on numerical data processed with inferential statistical data to determine the influence between variables. The sample size consists of 94 respondents. Instrument testing involved validity and reliability tests. Data collection for this study utilized regression analysis with questionnaire data analysis techniques. The data analysis method involved statistical analysis with assistance from SPSS version 25 software. The research findings indicate a positive influence of labor union involvement on employee performance at PT. Panasonic Manufacturing Indonesia. Additionally, employment agreements also have a significant positive impact on employee performance. These factors suggest that active participation in labor unions and well-established employment agreements can enhance motivation and performance among employees in the company. This research contributes to understanding the dynamics of the relationship between labor unions, employment agreements, and employee performance in the context of the manufacturing industry. The practical implications of this research highlight the need for company management to consider the roles of labor unions and employment agreements in enhancing productivity and employee well-being. Furthermore, the results of this research can serve as a basis for the development of more effective human resource management policies and practices at PT. Panasonic Manufacturing Indonesia.